Educator Concept According to Hasan Langgulung - Hariyanto Hariyanto; Heru Saiful Anwar; Mashur al Mutahar (Educan : Jurnal Pendidikan Islam, 2022)
Learners are human beings who develop their potential. Morality has improved in learners with different characteristics of learners in the way they behave and in the way they think. Lack of interest in educated learning will make behavioral changes. The emergence of bad morals is given because learners cannot learn well so that learners think narrowly in the world of education. For learners who use the Internet poorly, the behavior of learners will be bad. Therefore, teachers must improve good education or immediately instill it in learners so that learners do not raise them wrongly. The purpose of this study is: (1) to learn the definition of learners when hassan langolung, (2) to know the task of learners when hassan langolung, (3) to know the characteristics of learners when good langolung. This search is used in the desktop search method. As for data collection using document methods, the analysis used by researchers is descriptive analysis and content analysis. Descriptive analysis is used to collect records containing factual information about the title of this discussion, while this analysis is used to draw some conclusions according to the data obtained by the researcher. This research was obtained with the following results: (1) The definition of learners when Hassan Langolung is a human being who has the ability to think, act, learn, character, motivation or human beings who are burdened with the task of solving problems that every student in society or outside society gets. (2) As for the task of the learner Hassan Langolung, we can know, namely to study cosmic and religious sciences, the ability of learners to work, and the abundance of experience. (3) While the characteristics of pima yali learners: middle and simple, good morals, humble, true, honest, thank you, guidance and mercy, love, compassion, and preservation of the tongue.